Density and viscosity of four binary mixtures of [C2mmim][NTf2]/[C4mmim][NTf2] + dimethyl carbonate/diethyl carbonate. (January 2019) - Mou, Lin; Chai, Yuying; Yang, Guizeng; Xia, Quan; Liu, Qingshan; Zheng, Qige; Zhang, Qingguo
Highlights: The binary mixtures of [C2 mmim][NTf2 ]/[C4 mmim][NTf2 ] + DMC/DEC were prepared. The density and dynamic viscosity of the binary mixtures were measured. The excess molar volumes and viscosity deviations were calculated. The properties were discussed with the extension of the alkyl chain of the cation. Abstract: Two hydrophobic ionic liquids (ILs) 1-alkyl-2, 3-dimethylimidazolium bis[(trifluoromethyl)sulfonyl]imide ([C2 mmim][NTf2 ] and [C4 mmim][NTf2 ]) were synthesized. The binary mixtures of the two ILs were prepared with dimethyl carbonate (DMC) or diethyl carbonate (DEC) over the entire mole fraction range, respectively. The density and viscosity of the binary mixtures were investigated at temperature ranging from 293.15 to 328.15 K. The excess molar volumes and viscosity deviations were calculated for the four binary mixtures. The effects of the extension of the alkyl chain of the cation on the above properties are discussed. The Redlich-Kister equation was used for the fitting of the excess molar volumes and viscosity deviations versus mole fraction. The thermal expansion coefficients of the systems were obtained according to the density.